2010
DOI: 10.1021/np9007365
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Bioactivity of Cyclotides from the Micronesian Plant Psychotria leptothyrsa

Abstract: Cyclotides, the largest known family of head-to-tail cyclic peptides, have approximately 30 amino acid residues with a complex structure containing a circular peptide backbone and a cystine knot. They are found in plants from the Violaceae and Rubiaceae families and are speculated to function in plant protection. In addition to their insecticidal properties, cyclotides display cytotoxic, anti-HIV, antimicrobial, and inhibition of neurotensin binding activities. Although cyclotides are present in all violaceous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 65 publications
3
76
0
Order By: Relevance
“…Hedyotide B2, surprisingly, has a linear structure because it lacks the essential Asn/Asp residue in the putative loop 6 of the cyclized form. Although few examples of linear cyclotides have been identified, they all belong to the Möbius subfamily (21)(22)(23). This makes hedyotide B2 the first linear variant or uncyclotide of the bracelet subfamily to be discovered.…”
Section: Journal Of Biological Chemistry 44835mentioning
confidence: 99%
See 2 more Smart Citations
“…Hedyotide B2, surprisingly, has a linear structure because it lacks the essential Asn/Asp residue in the putative loop 6 of the cyclized form. Although few examples of linear cyclotides have been identified, they all belong to the Möbius subfamily (21)(22)(23). This makes hedyotide B2 the first linear variant or uncyclotide of the bracelet subfamily to be discovered.…”
Section: Journal Of Biological Chemistry 44835mentioning
confidence: 99%
“…Recently, a few linear variants of cyclotides have been discovered (21,22). Their occurrences appear to be rare, with only two naturally occurring linear variants having been reported: violacin A from Viola odorata (21) and psyle C from Psychotria leptothyrsa (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both mutations can account for the failure in the biosynthesis of cyclotide-containing precursors to produce the characteristic cyclic peptide backbone of cyclotides. Although the functional correlation between the circular structure and bioactivity remains controversial, several linear cyclotides have been shown to retain the bioactivities comparable with their cyclic counter parts (18,23).…”
mentioning
confidence: 99%
“…Recently, a few linear variants of cyclotides (also known as uncyclotides) have been identified, including violacin A from Viola odorata (23), psyle C from Psychotria leptothyrsa (24), and hedyotide B2 from Hedyotis biflora (22). Genetic characterization showed that both violacin A and hedyotide B2 have similar biosynthetic processing (22,23).…”
mentioning
confidence: 99%